Energia eólica e sustentabilidade: impacto dos parques eólicos na temperatura da superfície e na vegetação da caatinga - Siqueira, Marina de (2024)
In recent years, the expansion of renewable energy technologies has been remarkable on a global scale. Wind energy, in particular, has played a crucial role in the pursuit of decarbonizing the energy matrix. However, it is important to recognize that the construction and operation of wind farms have significant impacts on the environment and local climate, altering the properties of the land surface and disturbing the interactions between the surface and the atmosphere. This study is dedicated to investigating the effects of the growth and installation of wind farms on land surface temperature (LST) and vegetation in the Caatinga biome of Rio Grande do Norte (RN), a region particularly vulnerable to climate change. Geolocation data of wind turbines located in RN, provided by the Agência Nacional de Energia Elétrica (ANEEL), were used. The turbines were grouped into 34 clusters using the DBSCAN method. LST and vegetation data were obtained from the MODIS sensor aboard the Aqua and Terra satellites over the period from 2004 to 2023 for LST and 2022 for vegetation, using both day and night measurements. These data were compared with reference values extracted from the Açu National Forest. The results pointed to a trend of nighttime warming and a decrease in the Enhanced Vegetation Index (EVI) values over the years. These analyses offer a more comprehensive understanding of the environmental impacts associated with wind farms, considering the specific context of the Caatinga and its interactions with climate change.